Spindle cell lipoma of the occipital region: A case report - Rakesh, Devika; Bhatia, Gaurav; Singh, Ravinder Pal; Singh, Aminder; Garg, Ramneesh (Indian Journal of Case Reports, 2020)
Spindle cell lipoma (SCL) is a slow-growing tumor and a rare histological variant of benign lipomatous tumors. Cytology and histology along with clinical presentation are paramount in arriving at the correct diagnosis of SCL. Herein, is a case of a 31-year-old male who presented with a swelling in the left occipital region, on which previously two attempts for excision were made and aborted due to uncontrolled bleeding. The high-resolution sonographic findings suggested arteriovenous component in the lesion, whereas, non-contrast computed tomography of the head was suggestive of a lipoma. The histopathological analysis confirmed the diagnosis of SCL. We describe this case to highlight the classic location and differential diagnosis of the lipoma variants present commonly in this anatomic region. In addition, we review the role of pre-operative imaging in scalp soft-tissue tumors in assisting the surgeon in establishing the diagnosis and designing the surgical approach.